Characteristics and Risk Factors of Spinal Fractures in Recreational Snowboarders Attending an Emergency Department in Japan. Issue 5 (September 2016) - Ishimaru, Daichi; Matsumoto, Kazu; Ogawa, Hiroyasu; Sumi, Hiroshi; Sumi, Yasuhiko; Akiyama, Haruhiko
Abstract : Objective: The purpose of this study was to elucidate the characteristics of spinal fractures during recreational snowboarding and to determine the risk factors for these fractures. Design: Case series study. Setting: The Oku-mino ski area during the 7-year period between the 2005 to 2006 and 2011 to 2012 skiing seasons. Participants: Eight thousand seven hundred twenty-three snowboarders with injures. Interventions: Cases involved snowboarders with spinal fractures; controls were snowboarders without spinal fractures. Main Outcome Measures: The characteristics of spinal fractures were assessed using a standard form and patient records, including radiographs. Multivariate regression analysis was performed to investigate risk factors for spinal fractures, including age, type of slope, snow condition, accident cause, self-reported skill level, experience level, and the use of protective equipment. Results: Of 8723 snowboarders with injuries, 431 snowboarders presented with spinal fractures (4.9%). The most common spinal fracture was isolated transverse process fracture in the lumbar spine (33.2%, n = 143), followed by compression type fracture in the lumbar spine (25.1%, n = 108). Age (20-39 years), terrain slopes (half-pipe/box/kicker/rail), and jump-landing failure were associated with a significantly high risk of spinal fracture. Conclusions: Among the recreational snowboarders, isolated transverse process fracture in the lumbar spine was the most frequent spinal fracture. Age (20-39 year old), terrain slopes, and jump-landing failure were found to be risk factors for spinal fracture. Clinical Relevance: Identification of characteristics and risk factors for spinal fractures during snowboarding is useful information to create a preventive strategy for the fractures and make snowboarding a safer sport.